EFFECT OF RENAL DENERVATION ON CARDIAC FUNCTION AND APOPTOSIS-RELATED GENES' EXPRESSION IN HEART FAILURE DOGS. (June 2018) - Xu, M.; Lu, C.Z.; Feng, Q.L.
Abstract : Objective: To observe the effects of RDN on cardiac function and apoptosis-related genes' expression in MI-HF dogs. Figure. No caption available. Design and method: Eighteen healthy mongrel dogs were randomly divided into normal group (n = 6), model group (n = 6) and treatment group (n = 6). MI-HF was established in model group and treatment group by anhydrous alcohol embolization. After heart failure model was established, dogs in the treatment group and model group proceeded bilateral renal artery ablation and bilateral renal arteriography, respectively. The cardiac function parameters were measured; the serum NT-ProBNP level was detected by ELISA; the degree of myocardial fibrosis was observed through masson staining; TUNEL method was used to observe cardiomyocyte apoptotsis and calculate the apoptosis index (AI). Relative expression of Bcl-2, Bax, Caspase-3 and GRP78 were detected using RT-PCR and WB. Renal artery HE staining and serum creatinine were conducted to access the the efficacy and safety of RDN. Results: No statistical differences between the baseline weight, HR, LVEDD, LVESD, LVEF, LVEDP and LVSP in all dogs. Before ablation, NT-ProBNP level increased in HF dogs(treatment group and model group) compared with normal dogs, while no difference between treatment group and model group. 4 weeks after ablation, compared with model group the NT-ProBNP values reduced in treatment group. NT-ProBNP level were higher in HF dogs. 4 weeks after ablation, compared with normal group the Bax, Caspase-3, GRP78 mRNA and protein level in myocardial tissue have increased, Bcl-2 mRNA and protein expression decreased and cardiomyocyte apoptotsis index increased in heart failure HF dogs (model group and treatment group) with statistical significance. Compared with model group, the level of Bax, Caspase-3, GRP78 decreased, Bcl-2 mRNA and protein expression increased, myocardial apoptosis index decreased in RDN treatment dogs with statistical significance. 4 weeks after ablation, HE staining showed that the sympathetic nerve distribution decreased significantly after RDN operation. Conclusions: RDN could improve cardiac function in MI-HF dogs, and we speculate that its mechanism may be related to the raise of Bcl-2 gene expression and lower of Bax, Caspase-3, GRP78 expression level by RDN.